The Effect of Unsteady Strength Training and EAA Supplementation on Performance Efficiency and Achievement in the Triple Jump Under 20 Years Old - Obaid, Muayad; Adheem, Aya; Abed, Hussein (Pubmedia Jurnal Pendidikan Olahraga, 2025)
The exercises contribute to increasing the range of motion of the working joints and increasing the elasticity of the muscles involved in the performance, taking into account each jumper's level in terms of distance and time. The second point relates to nutritional deficiencies, due to many coaches focusing on the physical aspect of the jumper in training sessions compared to the nutritional aspect, which is the foundation of the physical aspect. Furthermore, athletes do not understand the importance of nutritional supplements as much as they understand physical exercises. To improve performance efficiency and achievement in the triple jump competition, the researchers prepared unsteady strength exercises and EAS supplementation for triple jumpers randomly  (by lottery) from clubs in the Middle Euphrates region, the study population. The jumpers were divided into three  (experimental) groups of  (5) jumpers each. The objective was to develop the efficiency of the jump and its execution. After conducting the pre-measurements, the unsteady strength exercises prepared by the researchers were performed, and the supplement  (EAAs) was taken for a period of  (6) weeks at a rate of  (3) units per week. Then the post-measurements were conducted, and the results were positive, as it was shown that the unsteady strength exercises and the supplement  (EAAs) together had a positive effect on developing the efficiency of performance, motor transfer, and achievement of the study sample.